PORTRAIT OF QUALITY MANAGEMENT IN MADRASAH ALIYAH (MA) BASED ON ISLAMIC BOARDING SCHOOLS IN BANGKA (Jurnal Penelitian, 2024)
This study examines the practice of quality management in Islamic boarding school-based Madrasah (MA) in Bangka, with three subjects, namely MA Hidayatussalikin Pangkalpinang, MA Nurul Falah Air Mesu, and MA Al-Mujahirin Koba. The method used is descriptive qualitative with collection techniques ranging from interviews, documentation, to observation. Samples were obtained from respondents and trusted sources with purposive sampling techniques. The results of the study The three madrasahs implemented and developed quality management starting from planning, implementation, evaluation, and follow-up improvements that were very synergistic between madrasah management, pesantren management, and foundation management. The four processes of maintaining the quality of madrasahs include one aspect that ensures the continuity of the development of madrasahs and pesantren, namely the aspect of religious enthusiasm among madrasah residents. Religious enthusiasm is the main strength of madrasah management in implementing quality management in Islamic boarding school-based madrasahs in Bangka. Recommendation: This study suggests that the management of madrasas, Islamic boarding schools, and Islamic boarding school foundations should remain a quality team effort to improve quality, with structured roles and responsibilities, and become a model that can be an alternative concept for quality madrasa management.